The influence of laser cutting parameters on the heat-affected zone in fast-growing Malaysian wood species - Ahmad Sobri, Sharizal; Norizan, Mohd Natashah; Sobri, Mohd Sharizal; Hermawan, Andi; Mohamad Amini, Mohd Hazim; Mohamed, Mazlan; Wan Ismail, Wan Omar Ali Saifuddin; Mohamed Sultan, Al Amin (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Wood is a naturally occurring renewable resource widely used in various industries, including in construction, packaging, furniture, and paneling. In Malaysia, 80% of furniture products are made from wood, making it a crucial material in this sector. Laser cutting is an advanced machining technique that enhances precision and minimizes material waste, yet its thermal effects, particularly the heat-affected zone (HAZ), remain a challenge. This study investigates how laser cutting parameters—including the laser power, traverse speed, and focus position—affect HAZ formation in two fast-growing Malaysian wood species, Acacia mangium and Azadirachta excelsa. This research seeks to determine the optimal laser settings that minimize HAZ dimensions while maintaining cutting precision. A diode laser cutting system was used to analyze the effects of three laser power levels (800, 1500, and 2400 mW), three traverse speeds (2, 5, and 10 mm/s), and three focus positions (on-focus, +0.2 mm, and −0.2 mm). We employed statistical analysis, including a two-way ANOVA, to assess the significance of these parameters and their interactions (p < 0.001). The results indicate that a higher laser power and slower speeds significantly increase the HAZ’s width and depth, with Azadirachta excelsa exhibiting a greater HAZ width but shallower penetration compared to Acacia mangium. A slight above-focus position (+0.2 mm) reduces the HAZ’s width, whereas a below-focus position (−0.2 mm) increases the HAZ’s depth. The optimal parameters for minimizing HAZ dimensions while ensuring efficient cutting were identified as a 1500 mW laser power, a 10 mm/s traverse speed, and an on-focus position (0 mm). This study provides practical insights into laser parameter optimization for tropical wood species, contributing to improved precision in laser machining and sustainable wood processing practices. These findings support industries in adopting advanced, high-quality laser cutting techniques tailored to fast-growing wood resources.